An Error Analysis of Using Gerund Made by the Fourth Semester Students of English Department of UNINDRA - Widyawati, Wiwik Yully (Universitas PGRI Sumatera Barat, 2018)
The purpose of the study is to find out what kinds and the causes of errors are made by the students of the Fourth semester of the English department of university in using gerund. This method used descriptive qualitative method. The writer used optional test about gerund (gerund as subject, direct object, and after preposition) as the instrument. The sampling technique that was used in this research was random. The writer took thirty students as sample. The data was analyzed by description about the error each item. The findings of this research are by analyzing the students’ test about using gerund. And the second is this research covered three main categories of gerund are: gerund as subject, gerund as direct object and gerund after preposition.After the researcher had done the research, the researcher got the conclusion that the result of all test showed the comprehensible of the gerund in the fourth semester is very poor. Second, the result of errors in using gerund as subject is 25.7 %. Third, the result of errors of using gerund as direct object is 36.7 %. Fourth, The result of errors of using gerund after preposition is 38.3%.Then, based on percentage, errors of using of gerunds after preposition occupy the highest rank. Occupying the second rank is errors of using gerund as object. The lowest rank is errors of using gerund as subject. Almost the errors occurred It is because they still do not understand how to use and put gerund.Key words: error analysis, Gerund, and the fourth semester students‘ability.